Hematinic deficiencies and anemia in gastric parietal cell antibody-positive and -negative oral submucous fibrosis patients - Chun-Pin Chiang; Julia Yu-Fong Chang; Yu-Hsueh Wu; Andy Sun; Yi-Ping Wang; Hsin-Ming Chen (Elsevier, 2018)
Background/purpose: Previous studies showed that approximately 13-15% of male oral submucous fibrosis (OSF) patients are serum gastric parietal cell antibody (GPCA)-positive. This study assessed whether serum GPCA or OSF itself was a significant factor that caused hematinic deficiencies and anemia statuses in GPCA-positive or GPCA-negative OSF patients (GPCA+/OSF and GPCA−/OSF patients). Materials and methods: The frequencies of macrocytosis (mean corpuscular volume or MCV ≧ 100 fL) and blood hemoglobin (Hb), iron, vitamin B12 and folic acid deficiencies were determined and compared between any two of the four groups of 149 male OSF, 23 male GPCA+/OSF, and 126 male GPCA−/OSF patients and 149 age-matched male healthy control subjects. Results: All three groups of OSF patients (including 149 OSF, 23 GPCA+/OSF, and 126 GPCA−/OSF patients) had a significantly higher frequency of Hb, vitamin B12, or folic acid deficiency and of macrocytosis than 149 healthy control subjects (all P-values < 0.05). The 23 GPCA+/OSF patients did have a significantly lower mean serum vitamin B12 level and a significantly higher MCV or frequency of vitamin B12 deficiency than the 126 GPCA−/OSF patients. Two of the 23 GPCA+/OSF patients had pernicious anemia. Of the 126 GPCA−/OSF patients, 6 had macrocytic anemia, 2 had iron deficiency anemia, and 4 had thalassemia trait-induced anemia. Conclusion: We conclude that OSF itself does play a significant role in causing hematinic deficiencies and anemia in OSF, GPCA+/OSF, and GPCA−/OSF patients. The serum GPCA is the major factor that causes vitamin B12 deficiency, macrocytosis, and pernicious anemia in GPCA+/OSF patients. Keywords: Anemia, Folic acid deficiency, Hemoglobin, Vitamin B12 deficiency, Gastric parietal cell antibody, Oral submucous fibrosis